Cytotoxic edema and diffusion restriction as an early pathoradiologic marker in canavan disease: case report and review of the literature. Issue 1 (December 2016) - Merrill, Steven; Nelson, Gary; Longo, Nicola; Bonkowsky, Joshua
Abstract Background Canavan disease is a devastating autosomal recessive leukodystrophy leading to spongiform degeneration of the white matter. There is no cure or treatment for Canavan disease, and disease progression is poorly understood. Results We report a new presentation of a patient found to have Canavan disease; brain magnetic resonance imaging (MRI) revealed white matter cytotoxic edema, indicative of an acute active destructive process. We performed a comprehensive review of published cases of Canavan disease reporting brain MRI findings, and found that cytotoxic brain edema is frequently reported in early Canavan disease. Conclusions Our results and the literature review support the notion of an acute phase in Canavan disease progression. These findings suggest that there is a window available for therapeutic intervention and support the need for early identification of patients with Canavan disease.